INTERCULTURAL COMMUNICATION AS AN INTERDISCIPLINARY SCIENCE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Humans are not the only carriers of culture—biologists and psychologists assert that some animals (particularly great apes) are capable of developing and transmitting culture. Thus, different animal populations can be considered as carriers of distinct cultures, and the interaction between these groups may also be referred to as intercultural communication. However, the theory of intercultural communication (ICC) does not study or analyze communication among animals. It is important to understand, though, that ICC is a very ancient phenomenon that emerged simultaneously with the formation of what we now cal different cultures.